2018
DOI: 10.1002/dev.21746
|View full text |Cite
|
Sign up to set email alerts
|

Linking autonomic physiology and emotion regulation in preschoolers: The role of reactivity and recovery

Abstract: Physiological recovery from negative emotions may be important for effective self-regulation, but little is known about recovery processes in children. The current study investigated links between autonomic physiology, anger expressions, and emotion regulation in a sample of eighty-three 3.5-year-olds. Respiratory sinus arrhythmia and pre-ejection period were measured during an anger induction task as parasympathetic and sympathetic indices, respectively. We examined whether preschoolers' anger expressions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 72 publications
(136 reference statements)
2
51
2
1
Order By: Relevance
“…However, studies are pointing to the importance of differential modeling of RSA such as linear and quadratic effects of RSA across different tasks and different developmental stages (Cui et al, ). Furthermore, in addition to resting RSA and RSA reactivity, some suggest that individual differences in RSA recovery from a stressor back to rest may also reflect a key process in regulation (Kahle, Miller, Helm, & Hastings ). Thus, future research would benefit from comparing models of RSA to identify those that are most appropriate and informative for the study of emotion regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies are pointing to the importance of differential modeling of RSA such as linear and quadratic effects of RSA across different tasks and different developmental stages (Cui et al, ). Furthermore, in addition to resting RSA and RSA reactivity, some suggest that individual differences in RSA recovery from a stressor back to rest may also reflect a key process in regulation (Kahle, Miller, Helm, & Hastings ). Thus, future research would benefit from comparing models of RSA to identify those that are most appropriate and informative for the study of emotion regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in addition to resting RSA and RSA reactivity, some suggest that individual differences in RSA recovery from a stressor back to rest may also reflect a key process in regulation (Kahle, Miller, Helm, & Hastings 2018). Thus, future research would benefit from comparing models of RSA to identify those that are most appropriate and informative for the study of emotion regulation.…”
Section: Strengths Limitations and Implications For Research And mentioning
confidence: 99%
“…Critical for investigations of self‐regulation in particular, at least one study has demonstrated links between autonomic recovery and the use of different self‐regulatory strategies (Kahle, Miller, Helm, & Hastings, ). This work showed that, in response to a frustration induction, a disengagement strategy was linked with less sympathetic arousal concurrently (reactivity) while greater use of engagement strategies was associated with increased sympathetic reactivity.…”
Section: Temporally Immediate Contexts Of the Psychobiology Of Self‐rmentioning
confidence: 99%
“…The same participating infants were also brought into the laboratory where we measured their reactivity while administering an attention task to measure visual sustained attention, and a behavioural task (still‐face protocol) to measure emotion reactivity. Early atypical performance on both of these tasks has been linked to a range of later psychopathologies (Johnson, Gliga, Jones, & Charman, ; Jones, Gliga, Bedford, Charman, & Johnson, ; Kahle, Miller, Helm, & Hastings, ; Santucci et al., ). Autonomic arousal was assessed using a combination of electrocardiography (ECG), heart rate variability and actigraphy (Cacioppo, Tassinary, & Berntson, ).…”
Section: Introductionmentioning
confidence: 99%